(untitled) (Baghdad Science Journal, 2011)
A total of 37 Staphylococcus epidermidis isolates, isolated from corneal scraping of patients with bacterial keratitis and 20 isolates from healthy eyes (as control) (all isolates, isolated from, Ibn Al- Haietham eye hospital / Baghdad), were tested for slime production, 52.63% of all isolates were positive-slime production (23 isolates from patients and 7 isolates from controls). It was found that positive-slime producing S. epidermidis were exhibited a high resistance to antibiotics as compared to negative-slime producing isolates.